Cybersecurity in the support services to occupational physicians in the city of Lima. A pilot study - Gomero, Raúl (2024)
Recent investigations emphasize the importance of cybersecurity in the growing digital era; 83% of organizations experienced breaks in cyber security in 2022, spending a mean of 4,35 million dollars per incident. Cybersecurity in Peru is regulated by legal norms aimed at protecting data and providing informatic security. Objective: To describe cybersecurity in the support services to occupational physicians (SSOP) in the city of Lima. Methods: A non-validated survey was created and distributed to 11 SSOPs in Lima that provide a service to an important building project in Lima. Results: More than 80% of health care establishments had a response plan against cybernetic attacks; security copies of the data were done regularly storing them in a different place than the establishment and regularly updated security software’s. Conclusion: The cybersecurity program is reactive. We discuss the importance of cybersecurity and analyze future challenges as well as emphasize the importance of preemptive preparedness in an environment of constant digital transformation.